Finite element analysis of the monitored long-term settlement behaviour of kouris earth dam in Cyprus - Pelecanos, Loizos; Skarlatos, Dimitrios; Pantazis, George (My University, 2018)
This paper presents a finite-element analysis of the long-term (>25 years) deformations of an earth dam. The aim is to examine the influence of (a) consolidation, (b) reservoir level changes and (c) seismic activity on the global deformations of embankment dams. The monitored long-term deformation behaviour of Kouris earth dam is analysed. Analysis of the field displacement data shows a consistent settlement trend with the time. Hydro-mechanical nonlinear finite-element analyses of the dam are conducted considering plasticity, small-strain stiffness and permeability. The stress history of the dam is modelled, including staged construction, reservoir impoundment, consolidation and seasonal reservoir level changes. It is shown that (a) seasonal reservoir level changes result in small fluctuations of dam settlements (i.e. vertical displacements), (b) horizontal dam crest displacements are insensitive to reservoir level changes and (c) the majority of the total settlements is due to soil consolidation.
Keywords: Cofferdams; Deformation; Seismic activity; Consolidation; Reservoir